A corpus-based analysis of discourse marker 'like' functions in podcasts: A gender study - Surya Putri, Zahrotul Nur Azizah; Nugroho, Suray Agung (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2023)
Focusing on the use of discourse markers (DM), this study investigated the use of DM like in dyadic communication in American Spotify podcasts. This research aimed to understand the linguistic behavior of podcasters in using DM like during their podcasts and to compare the spoken corpus of female and male speakers collected from the podcast. Corpus analysis assisted by AntConc 3.5.9. was applied to determine (1) which gender primarily used DM like within the corpus, (2) the significance between the usage of DM like and the speaker's gender, and (3) the functions of using DM like by each gender based on Mí¼ller's (2005) taxonomy of DM like functions. The analysis portrayed that male speakers prefer to use DM like more than female podcast speakers, which is in contrast to previous studies claiming that female speakers used more DM like than male speakers. The difference in results could be attributed to the 17-year gap in the study, which has potentially led to changes in the inclination of using DM like between genders. However, despite male speakers' higher usage of DM like, there is still no correlation between the use of DM like and the speaker's gender, aligning with previous research. Lastly, this study revealed that both genders used the same DM like functions, although the occurrences varied.